2021
DOI: 10.1021/acs.inorgchem.1c01120
|View full text |Cite
|
Sign up to set email alerts
|

Defect Engineering of Nanoscale Hf-Based Metal–Organic Frameworks for Highly Efficient Iodine Capture

Abstract: With the rapid development of the nuclear industry, how to deal with radioactive iodine waste in a timely and effective manner has become an important issue to be solved urgently. Herein, the defect-engineering strategy has been applied to develop a metal–organic framework (MOF)-based solid adsorbent by using the classical UiO-type Hf-UiO-66 as an example. After simple acid treatment, the produced defect-containing Hf-UiO-66 (DHUN) not only retains its topological structure, high crystallization, and regular s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 60 publications
1
26
0
Order By: Relevance
“…[24] These reports dealt with the use of iodine vapor generated in a closed cell, in contact with the considered powdered UiO-n compounds, which are then weighted for the estimation of iodine uptake. For this UiO-n series, other works also described the influence of defects in the UiO-66 (Hf) solids [25] or the effects of the nature of a wide variety of functional organic groups decorating the ditopic ligands in UiO-66, [26] by analyzing the iodine sorption from liquid phase using cyclohexane as solvent.…”
Section: Introductionmentioning
confidence: 99%
“…[24] These reports dealt with the use of iodine vapor generated in a closed cell, in contact with the considered powdered UiO-n compounds, which are then weighted for the estimation of iodine uptake. For this UiO-n series, other works also described the influence of defects in the UiO-66 (Hf) solids [25] or the effects of the nature of a wide variety of functional organic groups decorating the ditopic ligands in UiO-66, [26] by analyzing the iodine sorption from liquid phase using cyclohexane as solvent.…”
Section: Introductionmentioning
confidence: 99%
“…Because the chemical scrubbing methods currently used in reprocessing facilities face recyclability issues, , numerous strategies for efficient removal of radioactive I 2 have been devised mainly on the basis of the development of novel and effective adsorbents. Accordingly, a new generation of solid adsorbents that are very promising for I 2 reprocessing like porous polymers, graphene-based nanomaterials, zeolites, and covalent– and metal–organic frameworks (COFs and MOFs, respectively) has been developed. , Among them, organic–inorganic hybrid crystalline materials are very promising not only because of their efficiency but also because of their atomically precise structures, which makes it possible to elucidate the mechanism of I 2 uptake and release. For example, Yao recently reported mesoporous crystalline material assembled with aluminum–oxo carboxylate rings as the hosts for uptake of I 2 guests.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the correlation between the UV absorbance of iodine at 523 nm and time is plotted to study the adsorption process in detail (Figure S31). The result suggested that the adsorption rate of iodine was very fast initially and then become steady in an exponential manner ( R 2 = 99.76%) . As far as we know, the speed is faster than any other materials reported in the literature (Table S3).…”
Section: Resultsmentioning
confidence: 71%